The Implementation of Local Wisdom-Themed Poetry Musicalization Model and Its Influence on Elementary Students’ Poetry Writing and Reading Skills - Anggy Giri Prawiyogi; Rahman Rahman; Andoyo Sastromiharjo; Aang Solahudin Anwar; Tarpan Suparman (STAI Hubbulwathan Duri, 2023)
This paper set out to detail how using musicalization models based on poetry with a focus on local wisdom might improve students' abilities to read and write poetry in the primary school setting. The methodology of this investigation is quantitative. Nonequivalent Control Group Design was utilised for this study, making it a type of quasi-experimental research. This study was conducted at a randomly selected school in Purwakarta. The fifth-graders there split their time between two classes. Methods of data collecting, including both test and non-test methods. Students are tested using an assignment to write poetry, while knowledge is gauged using a reading comprehension form. If all of the prerequisites were met, a t-test was utilised for statistical significance in the data analysis. The study found that teaching primary school students about poetry through musicalization considerably increased their comprehension of the material. This can be shown by comparing pre-and post-test results on children's proficiency in reading and producing poetry using this framework. Students' interest in learning and their ability to write and read poetry benefit from a musical poetry model centred on local knowledge. Their vocabulary is enriched and expanded by the students' early exposure to Purwakarta's sites of local wisdom. Students found it less challenging to select appropriate diction when writing poetry. The students who enjoy making music out of their writing are given an additional creative challenge. Therefore, it appears that a musicalization model with a focus on wisdom can be useful for teaching poetry in primary schools in the modern period of education, which places an emphasis on writing and technology engagement without neglecting the wealth of students' local wisdom.